A study on the preferences of male students in choosing maritime courses - Besana, Ma. Catherine; Fernandez, Joshemel; Guamen, Ronald Rey; Puing, Jean; Silmete, Joenaflor
This study is about the "Preferences of Male Students choosing maritimeCourses" a way to determine factors affecting male students in choosing maritime courses. The reasons for choosing marine related courses and other relevant data that are significant to this study are identified. The respondents were students from John B. lacson Colleges Foundation Molo and Villa Iloilo City. They were classified according to their courses, specifically Marine engineering and marine Transportation. The researchers distributed one hundred questionnaires to each courses as mentioned above Marine Engineering and Marine Transportation. From these total respondents, one hundred were choses randomly and were used in data analyses. Questionnaires were given out as instrument of the said study and was complemented by interviews with the respondents. Answers were then tabulated and analyzed to facilitate its interpretation.